P3.204 HIV Risk Behaviour Among Men Who Have Sex with Men in Yangzhou and Guangzhou China: A Cohort Study. (13th July 2013) - Wang, Q; Yin, Y; Chen, X; Liang, G; Wang, B; Zhang, R; Jiang, N
Abstract : Background: This study provides the HIV prevalence, HIV incidence, HIV risk-factors, and demographics of Yangzhou MSM and a comparison of HIV risk behaviour among Yangzhou and Guangzhou MSM in China. Methods: A cross-sectional study and a prospective cohort study were conducted among MSM in Yangzhou and Guangzhou from July 2009 to September 2010. A total of 617 MSM (317 Guangzhou, 305Yangzhou) were screened for eligibility. Results: Compared with Guangzhou sample, Yangzhou sample was significantly older and lower educated and less likely to identify themselves as homosexual(p < 0.001), but more likely to be married (p < 0.001), and more likely to sex intercourse with female (p < 0.001). No significant differences were found in receiving more than 5 sexual health services in two samples (p > 0.05) and the proportions never or not always using condoms during sex with female and always use condoms in such a case (p > 0.05). A higher prevalence of HIV and syphilis was found among Yangzhou sample than Guangzhou sample (p < 0.001). Aged (older than 40 years), married, and syphilis-positive were associated with HIV infection in both samples In Multivariate logistic regression analysis. Conclusions: There were significantly differences in demographic characteristics and risk sexual behaviours and the prevalence and incidence of HIV and syphilis between Yangzhou sample and Guangzhou sample. Our results showed that Yangzhou sample was at higher risk of infection of HIV than Guangzhou sample and reinforced the strong need for more and further investigation targeting MSM in economic-medium cities to prevent HIV in China.